2021
DOI: 10.21037/jtd-21-126
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of FGF19 predicts poor prognosis in patients with non-small cell lung cancer

Abstract: Background: Lung cancer is one of the most common cancers and a leading cause of cancer-related death worldwide. Although many treatment options exist for lung cancer, some patients still suffer postoperative recurrence, and a consequent reduction of overall survival (OS). Our study aimed to investigate the correlation of FGF19 expression with the clinicopathological features and survival outcomes of non-small cell lung cancer (NSCLC) patients.Methods: Bioinformatics analysis was conducted using the data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…FGF19 can promote the occurrence of colorectal cancer by regulating metabolic biological functions, such as bile acid biosynthesis and insulin resistance ( Peng et al, 2020 ). The expression of FGF19 is significantly up-regulated in non-small cell lung cancer, and is associated with poor prognosis ( Chen et al, 2021a ). FGF19 stimulates cell proliferation and invasion by activating AKT-MAPK signaling pathway ( Hu & Cong, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…FGF19 can promote the occurrence of colorectal cancer by regulating metabolic biological functions, such as bile acid biosynthesis and insulin resistance ( Peng et al, 2020 ). The expression of FGF19 is significantly up-regulated in non-small cell lung cancer, and is associated with poor prognosis ( Chen et al, 2021a ). FGF19 stimulates cell proliferation and invasion by activating AKT-MAPK signaling pathway ( Hu & Cong, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…S1 ). In order to classify samples into high or low expression groups, we used the cut-off levels of 50% for nuclear and cytoplasmic VDR expression, 28 and 10% for nuclear p21 expression. For cytoplasmic p21, CYP27B1, CYP24A1, and E-cadherin, a score of 0–1 was categorized as negative, and a score of 2–3 was considered as positive ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study suggested that the occurrence and development of lung cancer are associated with the dysregulated expression and mutation of oncogenes and tumor suppressor genes ( 8 ), and a number of proteins and non-coding RNAs have been demonstrated to be involved in the pathogenesis of the disease ( 9 , 10 ). Previous studies have demonstrated that Musashi 2 and fibroblast growth factor 19 act as independent prognostic biomarkers in non-small cell lung cancer (NSCLC) ( 11 , 12 ). Mitotic spindle organizing protein 2A overexpression promotes NSCLC cell proliferation and invasion, which is associated with poor NSCLC prognosis ( 13 ).…”
Section: Introductionmentioning
confidence: 99%